Potret Budaya Organisasi MA Al-Amiriyyah Blokagung Tegalsari Banyuwangi - Siti Aimah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2019)
Every Islamic educational institution needs to have an organizational design based on the vision, mission, values, assumptions and goals that have been set. These philosophies and assumptions are known as organizational culture. Organizational culture is needed to change individual behavior into organizational behavior. Therefore, it will explain: (1) The Meaning of Organizational Culture; (2) Organizational Culture Level; (3) How Organizational Culture Begins (4) The Role of Organizational Culture; (5) Implementation of Organizational Culture; (6) Building a Strong Culture in the Organization (7) Recognizing the Environment and Adaptation Process; (8) Organizational Culture at Madrasah Aliyah Amiriyyah Blokagung Tegalsari Banyuwangi; (9) The Role of Leaders in Socialization and Implementation of Organizational Culture at MA al-Amiriyyah Blokagung Tegalsari Banyuwangi. In simple terms this study can be concluded that organizational culture is defined as a set of assumptions that are built and shared by organizations as moral in adapting to the external environment and the internal integration process. Among them are organizational processes, artifacts; values; and the basic assumptions that the founders of the organization have traditionally influenced. The organizational culture in Madrasah Aliyah al-Amiriyyah Blokagung is divided into three areas, namely: (1). Religious culture, Islamic boarding school activities; (2) Indonesian Culture, (3) Humanity Culture. Those are also supported by the role of the leader in the socialization and implementation of organizational culture at Madrasah Aliyah al-Amiriyyah which is done in writing and not in writing.